Mapping Genomic Regions for Grain Protein Content and Quality Traits in Milled Rice (Oryza sativa L.) - Violina Bharali; Suneetha Yadla; Srinivas Thati; Bhargavi Bitra; Divya Karapati; Neeraja Naga Chirravuri; Jyothi Badri; Raman Meenakshi Sundaram; Aravind Kumar Jukanti (Plants)
Grain protein content (GPC) is gaining attention due to increasing consumer demand for nutritious foods. The present study carried out at ICAR-IIRR, Hyderabad, focused on the identification of quantitative trait loci (QTLs) linked with GPC and other quality traits. We utilized a population of 188 F2 individuals developed from BPT 5204 (low GPC) X JAK 686 (high GPC) for QTL analysis. QTL analysis yielded four significant QTLs for GPC, three for amylose content, and multiple QTLs for other quality traits. qPC1.2, a major QTL in milled rice, was located in the marker interval RM562-RM11307 on chromosome 1 with an LOD value of 4.4. qPC1.2 explained 15.71% of the phenotypic variance (PVE). Additionally, the Interval Mapping for Epistatic QTLs (IM-EPI) method detected 332 pairs of di-genic epistatic QTLs. Fifteen QTLs exhibited a positive additive effect, indicating that the contributing allele(s) was from JAK 686. Five F2 plants, viz., F2-140, F2-12, F2-7, F2-147, and F2-41, exhibited a high GPC of 14.67%, 14.36%, 14.32%, 13.60%, and 13.36%, respectively. Additionally, these plants also exhibited high per-plant grain yield (~17.0–29.0 g) with desirable agronomic traits. The QTLs identified are valuable resources for developing high-grain-protein varieties with high grain yield and desirable quality traits.